Physical activity is associated with neuromuscular and physical function in patients with multiple sclerosis independent of disease severity. Issue 5 (27th February 2021) - Rooney, Scott; Riemenschneider, Morten; Dalgas, Ulrik; Jørgensen, Marie-Louise K.; Michelsen, Anne-Sophie; Brønd, Jan C.; Hvid, Lars G.
Abstract: Purpose: Examine the association between physical activity and neuromuscular and physical function in patients with multiple sclerosis when also considering disease severity. Methods: 91 patients with multiple sclerosis were enrolled. Assessments included physical activity by 7-day thigh-worn accelerometry, knee extensor neuromuscular function by dynamometry (maximal isometric muscle strength, rate of force development (0–50 ms)), and physical function by 5× sit-to-stand, 2-min walk test, and timed 25 ft walk test. Physical activity tertile comparisons along with simple and multiple regressions (adjusting for age, gender, EDSS, time since diagnosis) were performed. Results: Physical activity tertiles revealed differences ( p  < 0.05) in maximal muscle strength (1.77 ≈ 1.97 < 2.28 Nm/kg), rate of force development (4.66 < 8.03 ≈ 10.55 Nm/kg/s), 5× sit-to-stand (11.4 ≈ 9.7 > 8.5 s), 2-min walk test (153 < 183 < 207 m), and timed 25 ft walk test (6.3 > 4.4 > 4.3 s). Moreover, physical activity was associated ( p  < 0.05) with maximal muscle strength and rate of force development ( r 2   =  0.13–0.15) along with 5× sit-to-stand, 2-min walk test, and timed 25 ft walk test ( r 2  = 0.18–0.24), also after adjusting for age + gender + EDSS + time since diagnosis ( r 2  = 0.25–0.37 and 0.24–0.52), with physical activity consistently being a strong predictor. Conclusions: Higher levels of physical activity are associated with greater neuromuscular and physical function in ambulatory patients with multiple sclerosis independent of disease severity. These findings emphasize the importance of performing regular physical activity at all stages of multiple sclerosis. IMPLICATIONS FOR REHABILITATION: Physical activity is associated with neuromuscular and physical function, independent of disease severity. Physical activity may be important in improving or preserving neuromuscular and physical function at all stages of ambulatory multiple sclerosis patients, yet longitudinal studies are warranted. Clinicians and rehabilitation professionals should encourage ambulatory patients at all stages of their disease to be as physically active as possible.